Architecture in Islam: An Analytical Study of the Design of the Islamic House in Contemporary Concepts: العمارة في الاسلام: دراسة تحليلية لتصميم المسكن الإسلامي في ظل المفاهيم التصميمية المعاصرة - Sahar Thiab (Journal of engineering sciences and information technology, 2017)
The emergence of modern theories of architecture generated a big change and formed a remarkable development in architecture and in its progress’ pace; this development caused a change in the appropriate standards ​​between the architectural space and its users. The degree to which the residential space utilizes the social and functional needs of its residents is closely related to the creation of special experience. Contemporary Studies has paid great attention to address these aspects in residential design solutions by proposing a variety of housing models. Hence, it is necessary to search for the architectural version of the analgesic that is best suited Jordanian family for its present and future requirements confirmed by the moral teachings of Islam as a religion of every time and place. In our research, we are trying to identify functional requirements and social needs that are adequate for housing the Jordanian family in an effort to develop these advantages and characteristics in line with the requirements of modern demands of these families. The research methodology is to understand housing in Islamic architecture and its relationship to its surroundings and the community, and monitor the modern transformations in modern housing architecture in Jordan. The research later adopts these forms and constrains as the evaluation criteria in the analytical study of the villa "Attebaa" taking an example a contemporary house of the architect Ayman Zuayter work. The research then concludes and recommends looking at housing architecture as a result of individuals need, which is reflected on the community as part.